Come ‘Esakan’ 1Allah! - Abd Razak, Dzulkifli (2010)
The arrival of 2010 is not quite pleasant. A decade has passed in a new century beginning with the Sept 11 2001 episode especially has placed the Muslims in a disorderly situation, making them to be stamped as “terrorists” and imposed various actions as if they were guilty. The Guatanamo camp was revived specially to imprison any suspects as long as there were grounds to do so. The then president of the United States of America, whether on purpose or not, used the term crusade in declaring war against the terrorists.